Psychotic experiences and psychological distress in adolescents: an examination of longitudinal bidirectional effects across sex - Feten Fekih-Romdhane; Lilia Houissa; Alexandre Andrade Loch; Majda Cheour; Souheil Hallit (Child and Adolescent Psychiatry and Mental Health, 2024)
Abstract Background Although the co-occurrence of psychotic experiences (PEs) and psychological distress symptoms is growingly recognized in several previous studies, there is still a lack of literature, which clearly outlines how these two psychopathological entities affect each other over time. This study is intended to add to the literature by examining: (a) the longitudinal, bidirectional associations between PEs and psychological distress in a sample of Tunisian adolescents, and (b) whether these associations are moderated by sex. Methods 510 adolescent students (mean age of 16.05 ± 1.01 years, 61.2% females) took part in a prospective longitudinal study. PEs and psychological distress were measured at three occasions over a one-year period. The cross-lagged panel modeling approach was adopted. Results The current results showed that the experience of PEs at baseline tended to temporally precede prospective increases in psychological distress (at 6 months), which had in turn led to further exacerbation of psychological distress at 12 months of follow-up. Temporally primary psychological distress symptoms were not a significant predictor for the development of later psychotic symptoms in the whole sample. However, temporal patterns between adolescent distress and psychotic symptoms differed for girls and boys. Endorsing PEs at baseline was followed by greater psychological distress at 6 months, which was in turn associated with a significant increased risk of subsequent exacerbation of PEs at 12 months in boys, whereas psychological distress at 12-month follow-up was significantly predicted by pre-existing PEs in girls. Conclusion These findings suggest that clinicians and support workers are recommended to take into account different social risk profiles for boys and girls when considering interventions to address PEs and distress in adolescents.